Influence of national income, population, and waste emissions on food security utilization: New evidence related to Saudi Arabia's obesity - Elzaki, Raga; Tami, Suzan; Al-Mahish, Mohammed (Edelweiss Applied Science and Technology, 2025)
The prevalence of obesity in Saudi Arabia has been steadily increasing. This study aims to investigate the effects of urban population, national income, and waste emission shocks on obesity prevalence in Saudi Arabia. It utilizes annual time series data and applies the vector autoregressive (VAR) model, along with diagnostic tests including Granger causality, impulse response functions (IRFs), and forecast error variance decompositions (FEVDs). The results confirm that urban population and national income are the primary drivers of obesity prevalence in Saudi Arabia. Granger causality was observed between obesity, urban population, and waste emissions. The cumulative effects of shocks to the urban population, national income, and waste emissions significantly influence variations in obesity prevalence over time. The forecast error variance of obesity can be attributed mainly to urban population shocks. Policymakers should prioritize integrated urban planning, economic, and environmental strategies that promote healthy lifestyles, reduce socioeconomic disparities, and ensure sustainable living conditions. Coordinated efforts among public health, urban development, and economic sectors are essential to address obesity and its underlying determinants.